Application of the discovery learning model using student worksheets based on scaffolding on stoichiometric materials to improve learning outcomes - Maysara; Wahyuni, Wa Ode Aulia; Marhadi, Muh Alim; Dahlan; Haetami, Aceng; Esnawi (International Journal of Educational Technology and Learning, 2024)
This research endeavours to achieve three primary objectives: firstly, to assess the learning outcomes of class X students instructed through the discovery learning model and class; secondly, to evaluate the effectiveness of these learning outcomes; and thirdly, to discern any significant differences in learning outcomes between students taught through the standard discovery learning model and those taught with the incorporation of a scaffolding-based Student Worksheet. The research method employed is quasi-experimental, utilizing a non-equivalent pretest-post-test control group design to gather comprehensive insights. Data collection involves the strategic use of pre-tests, post-tests, and observation sheets to capture nuanced aspects of the learning process. The findings of the research indicate that the application of the discovery learning model, complemented by scaffolding-based Student Worksheets in stoichiometry learning, has a transformative impact. It is observed that students exposed to this method exhibit heightened engagement, reflected in their learning activities categorized as 'very good.' The calculated learning effectiveness, quantified by a substantial n-gain value of 0.71, attests to the high efficacy of this pedagogical approach, placing it in the 'high' category. These results carry significant implications for educational practitioners and curriculum developers. Educators can leverage the discovery learning model augmented with scaffolding-based Student Worksheets to enhance student participation and comprehension in stoichiometry. The demonstrated effectiveness of this approach suggests its potential integration into chemistry education methodologies, promising improved learning outcomes.